Ah! amada Amanda: a contação de história como subsídio para trabalhar a supressão da consoante nasal em posição de coda silábica - Lima, Joyce dos Santos (2020)
If in writing we generally observe particular elements of speech, in the literacy process this influence is even more evident. This transposition between different codes implies orthographic variation that take time to be remedied and may even incur fossilization. Therefore, teachers should be aware of the interference of speech in writing in the literacy process. In this perspective, this research report addresses the most incident phonological processes in the early grades of elementary school, in particular, the suppression of the nasal in syllable code position at the beginning of the written language acquisition process. The study and the resulting practice took place at Dom Pedro II Municipal School, located in Pedra Branca Village, Laranjeiras / SE, in the 1st year of elementary school. The work, in general terms, comprises: (1) an entrance test, which helped us to identify recurrent errors, (2) an intervention activity and (3) an exit test that aimed to verify if the strategies used were successful, positive for student literacy. The first step, which consisted of a visual dictation, showed that, in general, students still did not distinguish between oral or nasal vowels. The second stage, then, engaged in a sequence of activities that included the preparation of a book illustrated by the students and a game called Trilha, trilando. The third stage had an similar activity to the entrance test and we could verify that there was a considerable improvement in the spelling of words that has nasal in final syllable position. We are supported by the guiding documents of education in Brazil, such as the BNCC and NCPs and authors such as Magda Soares (2008) to address literacy and literacy and Scliar Cabral (2003), Cagliari (2009), Lamprecht (2009), Cristofaro- Silva (2011), among others, to deal with phonological issues. We realized that storytelling followed by playful activities are important strategies for the approaching of language issues that emerge daily in classrooms. The present work collaborated with the phonological awareness of children and intends to arouse in teachers the importance of considering orality in the literacy process.